Wideband Planar Antenna for New Generation Mobile Applications. (15th May 2007) - Bybi, P. C.; Jitha, B.; Mohanan, P.; Aanandan, C. K.
Abstract : A wideband, compact planar monopole antenna having a 2: 1 VSWR bandwidth of 98% (1.68 GHz–4.9 GHz) is presented. The omnidirectional radiation pattern with moderate gain and linear polarization in the entire band makes the antenna an excellent candidate for new generation mobile applications. Details of the antenna design and a comparison of simulated and measured results are presented and discussed.